Integrating Compliance: The Strategic Intermediary Role of Tax Agents in Audit Assurance through A Systematic Literature Review - Nor Asiah Taib; Izlawanie Muhammad; Suhaila Abdul Hamid (Universal Publishers - Boca Raton, Florida, USA, 2026)
Indexed by ERA